Destructive and Nondestructive Tests for Concrete Containing a Various Types of Fibers - Muthana Sh. Mahdi; Ihab S. Saleh; Saddam Kh. Faleh (Civil Engineering Journal, 2022)
Fibers have been considered an effective material that was used to improve the concrete's weak properties, namely its tensile strength, ductility, and crack resistance. Thus, the current study highlights two major objective, the former is the fibers shapes and types on the mechanical properties of the fresh and hardened concrete while the latter explores the impact of the fiber contents on the concrete mechanical properties developments. To achieve these targets six types of fibers (five of them made of steel and the last was polyolefin fibers) with various shapes are utilized. The tests were carried out to investigate the fibers shape and material contribution in the concrete mix properties improvement. The samples were subjected to destructive and non-destructive tests such as workability, compression, bending, and splitting. The non-destructive tests include ultrasonic pulse velocities and the Schmidt Hammer test. Three kinds of fibers (two of steel and one of polyolefin fiber) are used with variable content ratios of 0.5, 0.75, 1.0, and 1.5% to study the fiber content effect. Generally, the workability of fresh concrete has a reverse relationship with fiber presence and fiber content ratios. The compressive capacity, splitting and flexural strength has a direct proportion with fibers contents. The hooked steel fibers appeared the best results in terms of shape comparison. Doi: 10.28991/CEJ-2022-08-11-07 Full Text: PDF